HEDONISM PRACTICES AS REFLECTED THROUGH MAIN CHARACTER IN THE WOLF OF WALL STREET MOVIE - Muhammad Ridho; Tri Wahyu Retno Ningsih (Jurusan Sastra Indonesia, 2020)
The objective of this research were to find out the hedonism practices through main character dialogues in The Wolf of Wall Street movie based on Weijers’s theory of hedonism and happiness which consist of six types of hedonism, they were folk hedonism, value and prudential hedonism, motivational hedonism, normative hedonism, hedonistic egoism, and hedonistic utilitarianism. This research used descriptive qualitative method to analyze the data. The data were taken from the main character dialogues in The Wolf of Wall Street movie. The result of the research showed that there were five types of hedonism practices found in the main character dialogues of The Wolf of Wall Street movie, they were folk hedonism, value and prudential hedonism, motivational hedonism, hedonistic egoism, and hedonistic utilitarianism.